User-Generated Content and Influencer Marketing in Fashion Retail: How User Engagement Mediates Purchase Intention on Shopee - Nathanael, Naomi; Utami, Christina Whidya (Dinasti Publisher, 2025)
The rapid expansion of e-commerce, particularly in the fashion retail sector, has emphasized the importance of digital marketing strategies such as user-generated content (UGC) and influencer marketing. This study investigates how UGC and influencer marketing influence consumers' purchase intention on Shopee, with user engagement as a mediating variable. Using a quantitative approach, data were collected through online surveys from 150 Shopee users who had encountered fashion-related content either from users or influencers. Structural Equation Modeling (SEM) was employed to analyze the relationships between variables. The findings reveal that both UGC and influencer marketing significantly enhance user engagement. However, neither UGC nor influencer marketing directly influences purchase intention without user engagement. User engagement fully mediates the effect of both variables on consumers’ intention to purchase. This implies that engaging users emotionally and interactively is crucial for converting digital exposure into buying decisions. The study underscores the importance of fostering authentic engagement through personalized content and strategic influencer partnerships. These insights offer practical implications for fashion brands and marketers in optimizing their social media strategies to drive online sales effectively.